AN ANALYSIS ON THE SPEAKING MATERIALS OF ENGLISH TEXTBOOK USED AT THE EIGHTH GRADE BASED ON CUNNINGSWORTH’S CRITERIA - Dewi Ernestia Simatupang; Sumarsih Sumarsih (Universitas Negeri Medan, 2022)
This study deals with the Cunningsworth’s criteria in speaking materials in Englishtextbook used at the eighth grade. The objective of this study was to determine whetherthe speaking materials in the English textbook